Targeting Epigenetic Modifiers Can Reduce the Clonogenic Capacities of Sézary Cells - Chebly, Alain; Prochazkova-Carlotti, Martina; Idrissi, Yamina; Bresson-Bepoldin, Laurence; Poglio, Sandrine; Farra, Chantal; Beylot-Barry, Marie; Merlio, Jean-Philippe; Tomb, Roland; Chevret, Edith (Frontiers in Oncology, 2021)
Sézary syndrome (SS) is an aggressive leukemic variant of cutaneous T-cell lymphomas (CTCL) in which the human Telomerase Reverse Transcriptase (hTERT) gene is re-expressed. Current available treatments do not provide long-term response. We previously reported that Histone deacetylase inhibitors (HDACi, romidespin and vorinostat) and a DNA methyltransferase inhibitor (DNMTi, 5-azacytidine) can reduce hTERT expression without altering the methylation level of hTERT promoter. Romidepsin and vorinostat are approved for CTCL treatment, while 5-azacytidine is approved for the treatment of several hematological disorders, but not for CTCL. Here, using the soft agar assay, we analyzed the functional effect of the aforementioned epidrugs on the clonogenic capacities of Sézary cells. Our data revealed that, besides hTERT downregulation, epidrugs' pressure reduced the proliferative and the tumor formation capacities in Sézary cells in vitro.